The Distance of Heaven: An Analysis of the Guodian Wu Xing - Matthew James HAMM (Asian Studies, 2017)
This paper argues that the Guodian Wu Xing consists of two interrelated sections that reflect its distinction between goodness (a characteristic of humans) and virtue (a trait of Heaven). Individually, each section emphasizes different aspects of self-cultivation. When read against one another, they articulate the text’s main argument that Heaven is a distant figure and that the sage, a figure who understands the Way of Heaven, is almost unreachable. As such, the text focuses on the gentleman, a figure who achieves virtue (defined as timeliness) within a dispositional context by emulating Heaven in accordance with the Way of the Gentleman.